2010
DOI: 10.2522/ptj.20090119
|View full text |Cite
|
Sign up to set email alerts
|

Sit-to-Stand Movement as a Performance-Based Measure for Patients With Total Knee Arthroplasty

Abstract: Implantation of a total knee prosthesis partly improved performance of the sit-to-stand movement. Participants in the TKA group could fully load their operated leg, but they could not generate enough knee angular velocity during rising compared with the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 38 publications
(20 reference statements)
2
58
1
Order By: Relevance
“…Surprisingly, however, the modified knee muscle co-activation strategy did not alter the overall movement duration, a finding that is not in line with previous studies reporting a longer STS duration in patients with advanced OA compared to healthy controls (Boonstra et al, 2010;Christiansen and Stevens-Lapsley, 2010;Turcot et al, 2012b). This discrepancy may have several explanations.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Surprisingly, however, the modified knee muscle co-activation strategy did not alter the overall movement duration, a finding that is not in line with previous studies reporting a longer STS duration in patients with advanced OA compared to healthy controls (Boonstra et al, 2010;Christiansen and Stevens-Lapsley, 2010;Turcot et al, 2012b). This discrepancy may have several explanations.…”
Section: Discussioncontrasting
confidence: 71%
“…contribution to overall movement duration by the two groups seems unlikely. Second, longer movement duration could be due to weight bearing asymmetries in patients with advanced knee OA (Boonstra et al, 2010;Christiansen and Stevens-Lapsley, 2010;Turcot et al, 2012b), which increases medio-lateral sway during chair rising. This loading occurs with the leaning of the trunk towards the unaffected leg, in order to unload the affected one.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have already demonstrated modifications in gait [1,2], stair-climbing [3,4], unipodal stance [5], and the sit-tostand (STS) task [6][7][8]. When compared with gait and stairclimbing, STS requires greater joint forces and moments [9].…”
Section: Introductionmentioning
confidence: 97%
“…They proposed that STS may be used to objectively evaluate the biomechanical knee function following a total knee arthroplasty (TKA) [12]. To our knowledge, only a few studies have used the STS task to investigate the functional disability of patients with advanced knee OA [6,7] or patients following a TKA [8,9,[12][13][14]. In those studies, the main parameters investigated were the weightbearing asymmetry [6,7,12,14], knee motion [9,13,14], knee angular velocity [6,12], and knee and hip joint moments [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation